PENGARUH MODEL PEMBELAJARAN TRADE A PROBLEM DENGAN PEMBERIAN REWARD TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS VII SMP N.1 GUNUNG MALELA - Christa Voni Roulina Sinaga (Universitas Islam Sumatera Utara, 2019)
Abstract. The purpose of this study was to determine the effect of the trade a problem learning model by rewarding students' mathematical communication skills. This type of research is quasi-experimental research by determining one class of research samples taken randomly as the experimental class. In this study the method of data retrieval is carried out by applying to an experimental class a treatment condition. The population in this study were all VII grade students of SMP N 1 Gunung Malelala. The results show a strong relationship between the Trade A Problem learning model and reward for students' communication skills. Based on the results of the calculation of the regression equation the equation ????̂=27,87+0,64???? is obtained. In this equation the regression direction coefficient (b) = 0.64 is positive, which means that the two variables have a positive linear relationship.Keywords: trade a problem, mathematical communication skills.